EDUCATION AND HEALTH IN THE DAILY PRACTICE OF PRIMARY CARE NURSES - Geyse Aline Rodrigues Dias; Márcia Maria Bragança Lopes (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927846 Aim: to unveil the daily educational practice of nurses in primary care. Method: exploratory research with qualitative approach, performed with four nurses from a family health Strategy Unit, located in Belém-Pará-Brazil. The data were collected through semi-structured interview and analyzed using the technique of Grounded Theory. Results: Were organized into two categories: The size of educational actions of nurses in primary care and the praxis of educational actions developed by nurses in the primary care, which demonstrated the predominance of the traditional model for information on health education and the lack of scientific knowledge applied in educational actions. Conclusion: it is believed that this health education is still a challenge, but that should be thought of as a process to be achieved by the professionals from health services, when developing educational practices focused on the reality of the population.